(untitled) (Bangladesh Journal of Medical Science, 2024)
Background The most prevalent sexual differentiation disorder in males is undescended testis (UDT), which occurs when the testis is absent from the scrotum or cannot be brought down during a physical examination. Pregnancy outcome may be influenced by the wife’s lifestyle and surgical correction within the past year Objectives This study aims to determine pregnancy outcome in Assisted Reproductive Technology (ART) on a wive with a UDT husband assessed by the wive’s life style and surgery correction before 1 year. Methods A cross-sectional study was conducted. Data were taken from patients who underwent Assisted Reproductive Technology at AMC Hospital, Yogyakarta. Data collection from 2018 to 2021. Samples in the unilateral and bilateral groups were 20 husbands. Wilcoxon Signed Rank Test helped carry out the analyses. Results There was an association between infertility and UDT either unilaterally or bilaterally (p = 0.009). Most UDT husbands had a BMI in the overweight category and the average age was 28 and 29. Other factors such as the wive’s life style and surgery correction before 1 year , including smoking habit, alcohol consumption, addictive drug and hormonal drug, had no significant effect on the success of pregnancy outcome (p > 0.05). Conclusions Although pregnancy outcome in unilateral and bilateral UDT patients was not statistically significant, clinically, the pregnancy outcome was better in husbands with unilateral UDT by IUI than in IVF. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 455-462